Immigrant Inventors and Diversity in the Age of Mass Migration - Francesco Campo; Mariapia Mendola; Andrea Morrison; Gianmarco Ottaviano (Institute of Labor Economics (IZA), 2020)
A possible unintended but damaging consequence of anti-immigrant rhetoric, and the policies it inspires, is that they may put high-skilled immigrants off more than low-skilled ones at times when countries and businesses intensify their competition for global talent. We investigate this argument following the location choices of thousands of immigrant inventors across US counties during the Age of Mass Migration. To do so we combine a unique USPTO historical patent dataset with Census data and exploit exogenous variation in both immigration flows and diversity induced by former settlements, WWI and the 1920s Immigration Acts. We find that co-ethnic networks play an important role in attracting immigrant inventors. However, we also find that immigrant diversity acts as an additional significant pull factor. This is mainly due to externalities that foster immigrant inventors' innovativeness. These findings are relevant for today's advanced economies that have become major receivers of migrant flows and, in a long-term perspective, have started thinking about immigration in terms of not only level but also composition.
Keywords: F22; J61; O31; 330; international migration; cultural diversity; innovation